2015
DOI: 10.1515/hf-2015-0088
|View full text |Cite
|
Sign up to set email alerts
|

N-Bromosuccinimide (NBS) – an efficient catalyst for acetylation of wood

Abstract: Solvent-free acetylation of rubberwood (Hevea brasiliensis Müll.Arg) with acetic anhydride (Ac 2 O) and by means of N-bromosuccinimide (NBS) as catalyst was carried out in an oil bath at 105°C and 120°C. The effect of catalyst concentration, temperature, and reaction time was studied. The extent of acetylation was measured by determining the weight percent gain (WPG), and the acetylated wood was characterized by FTIR-ATR, CP/MAS 13 C NMR, and XRD spectroscopy. The presence of NBS in concentrations between 1.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The use of Nbromosuccinimide (NBS) as catalyst has been demonstrated as a convenient and effective method. Nagarajappa et al (2015) [14] reported the full mechanism of the acetylation reaction using NBS catalysts, and cites that, others catalyst has also been used in acetylation reactions, such as pyridine, but the toxic nature and unpleasant odor make pyridine unsuitable for large-scale applications [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The use of Nbromosuccinimide (NBS) as catalyst has been demonstrated as a convenient and effective method. Nagarajappa et al (2015) [14] reported the full mechanism of the acetylation reaction using NBS catalysts, and cites that, others catalyst has also been used in acetylation reactions, such as pyridine, but the toxic nature and unpleasant odor make pyridine unsuitable for large-scale applications [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Specimens of W. tinctoria (size 150 mm x 3,5 mm x 5 mm) were acetylated with acetic anhydride using N-bromosuccinimide (NBS) as catalyst (concentration 2 % weight /volume) as per the procedure described by Nagarajappa et al 2015. Reaction was carried out in an oil bath (reaction conditions: temperature -105 °C, reaction time -4 h) in a glass vessel connected to a water condenser.…”
Section: Acetylation Of Woodmentioning
confidence: 99%
“…Compared to the polymer impregnation, chemical modification has more positive effects in water resistance and dimensional stability, because it can fundamentally reduce the amounts of hydroxyl groups. For example, acetylation involves the replacement of hydroxyl groups with acetyl groups of acetic anhydride (shown in Figure a). , The acetylated wood showed excellent dimensional stability, water resistance, and decay resistance. However, due to the environmental, economic, and technical concerns, only a few acetylation methods have led to commercialization …”
Section: Introductionmentioning
confidence: 99%